2017
DOI: 10.1177/0145445517715871
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Rule-Following in the Face of Reversed Reinforcement Contingencies: The Differential Impact of Direct Versus Derived Rules

Abstract: Rule-governed behavior and its role in generating insensitivity to direct contingencies of reinforcement have been implicated in human psychological suffering. In addition, the human capacity to engage in derived relational responding has also been used to explain specific human maladaptive behaviors, such as irrational fears. To date, however, very little research has attempted to integrate research on contingency insensitivity and derived relations. The current work sought to fill this gap. Across two experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 19 publications
4
45
2
Order By: Relevance
“…First, we expected participants who were given any type of (initially accurate) instruction to demonstrate evidence of the IE. In-line with previous work (e.g., Donadeli & Strapasson, 2015;Harte et al, 2017;Hayes et al, 1986c;Henley et al, 2017;Kudadjie-Gyamfi & Rachlin, 2001;Ninnes & Ninnes, 1998;Otto et al, 1999), we obtained support for this hypothesis, such that participants in the ply and track group were more likely than those in the no-instructions group to select the MLCS after the programmed contingency reversal.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…First, we expected participants who were given any type of (initially accurate) instruction to demonstrate evidence of the IE. In-line with previous work (e.g., Donadeli & Strapasson, 2015;Harte et al, 2017;Hayes et al, 1986c;Henley et al, 2017;Kudadjie-Gyamfi & Rachlin, 2001;Ninnes & Ninnes, 1998;Otto et al, 1999), we obtained support for this hypothesis, such that participants in the ply and track group were more likely than those in the no-instructions group to select the MLCS after the programmed contingency reversal.…”
Section: Discussionsupporting
confidence: 91%
“…Despite their advantages, rules and instructions can also undermine our contact with other contingencies in the environment. Indeed, research has repeatedly shown that once behavior is controlled by a rule, individuals may persistently follow that rule, even when doing so no longer produces the most beneficial outcome (e.g., Donadeli & Strapasson, 2015; Harte, Barnes-Holmes, Barnes-Holmes, & McEnteggart, 2017;Hayes, Brownstein, Haas, & Greenway, 1986;Hayes, Brownstein, Zettle, Rosenfarb, & Korn, 1986;Joyce & Chase, 1990;Kudadjie-Gyamfi & Rachlin, 2001;Miller, Hirst, Kaplan, DiGennaro Reed, & Reed, 2014;Ninnes & Ninnes, 1998;Otto, Torgrud, & Holborn, 1999). We refer to this insensitivity of behavior to the consequences of other (non-instructed) contingencies, as the instruction or rule-based "insensitivity effect (IE)" 1 .…”
Section: Examining the Moderating Impact Of Plys And Tracks On The Inmentioning
confidence: 99%
“…More recently, research has begun to extend this line of work and to examine the impact of derived relations on persistent rule-following or contingency-based insensitivity (Harte, et al, 2017). Across two experiments, Harte et al sought to determine the extent to which participants would persist in rule-following when the reinforcement contingencies were reversed, and thus following the rule was no longer rewarded.…”
Section: Introductionmentioning
confidence: 99%
“…One limitation of the Harte et al (2017) study, which was acknowledged by the authors, was the dichotomy made between direct and derived rule-following. Strictly speaking, for RFT even the direct rule condition involved a certain (low) level of derivation.…”
Section: Introductionmentioning
confidence: 99%
“…To date, however, very little research has attempted to integrate research on contingency insensitivity and derived relations. Our research group recently conducted a study that has attempted to fill this gap and the interpretation of the results has been greatly facilitated by the MDML (Harte, BarnesHolmes, Barnes-Holmes, & McEnteggart, 2017), and thus we will briefly consider this work here.…”
mentioning
confidence: 99%